NTNG1 Modulates Cisplatin Resistance in Epithelial Ovarian Cancer Cells via the GAS6/AXL/Akt Pathway - Fang, Shanyu; Luo, Yuanyuan; Zhang, Ying; Wang, Houmei; Liu, Qianfen; Li, Xinya; Yu, Tinghe (Frontiers in Cell and Developmental Biology, 2021)
Cisplatin resistance is a challenge in the treatment of epithelial ovarian cancer. Here, clinical data showed that the level of netrin-G1 (NTNG1) in cisplatin-resistant cancer was higher than that in cisplatin-sensitive cancer (2.2-fold, p = 0.005); patients with a high NTNG1 level in cancer tissues had shorter progression-free survival (11.0 vs. 25.0 months, p = 0.010) and platinum-free interval (5.0 vs. 20.0 months, p = 0.021) compared with patients with a low level. Category- or stage-adjusted analyses demonstrated that the association between the NTNG1 level and prognosis occurred in type II or FIGO III/IV cancer. The basal level of NTNG1 in SKOV3/DDP cells (a cisplatin-resistant subline) was higher than that in SKOV3 cells; therefore, NTNG1 was overexpressed in SKOV3 cells, or silenced in SKOV3/DDP cells. Knocking-in NTNG1 reduced the action of cisplatin to decrease cell death and apoptosis of SKOV3 cells, accompanied by upregulation of p-AXL, p-Akt, and RAD51; however, opposite effects were observed in SKOV3/DDP cells after knocking-down NTNG1. Co-immunoprecipitation demonstrated that NTNG1 bound GAS6/AXL. Silencing NTNG1 enhanced cisplatin effects in vivo, decreasing tumor volume/mass. These data suggested that a high NTNG1 level resulted in cisplatin resistance in ovarian cancer cells via the GAS6/AXL/Akt pathway, and that NTNG1 may be a useful target to overcome resistance.